Matrix Gla protein negatively regulates calcification of human aortic valve interstitial cells isolated from calcified aortic valves - Mari Chiyoya; Kazuhiko Seya; Zaiqiang Yu; Kazuyuki Daitoku; Shigeru Motomura; Tadaatsu Imaizumi; Ikuo Fukuda; Ken-Ichi Furukawa (Elsevier, 2018)
Calcified aortic valve stenosis (CAS) is a common heart valve disease in elderly people, and is mostly accompanied by ectopic valve calcification. We recently demonstrated that tumor necrosis factor-α (TNF-α) induces calcification of human aortic valve interstitial cells (HAVICs) obtained from CAS patients. In this study, we investigated the role of matrix Gla protein (MGP), a known calcification inhibitor that antagonizes bone morphogenetic protein 2 (BMP2) in TNF-α-induced calcification of HAVICs. HAVICs isolated from aortic valves were cultured, and calcification was significantly induced with 30 ng/mL TNF-α. Gene expression of the calcigenic marker, BMP2, was significantly increased in response to TNF-α, while the gene and protein expression of MGP was strongly decreased. To confirm the role of MGP, MGP-knockdown HAVICs and HAVICs overexpressing MGP were generated. In HAVICs, in which MGP expression was inhibited by small interfering RNA, calcification and BMP2 gene expression were induced following long-term culture for 32 days in the absence of TNF-α. In contrast, HAVICs overexpressing MGP had significantly decreased TNF-α-induced calcification. These results suggest that MGP acts as a negative regulator of HAVIC calcification, and as such, may be helpful in the development of new therapies for ectopic calcification of the aortic valve. Keywords: Aortic valve stenosis, Human aortic valve interstitial cells, Matrix Gla protein, Aortic valve calcification